Perbedaan Communication Back Massage dan Back Massage dalam Menurunkan Tekanan Darah Pada Klien dengan Lansia dengan Hipertensi - Rizal Arifin; Harmayetty Harmayetty; Sriyono Sriyono (Universitas Airlangga, 2019)
Introduction: There are many drugs in the effort to cure hypertension for the old that in fact have bad influence because they cause dependence and are risky with misestimated doses. Communication back massage and back massage are two of complementary therapies recommended to lower blood pressure due to each relaxation effects are good. This study aims to clarify the difference of communication back maassage and back massage to reduce blood pressure. Method: This study was used quasy experimental design. The total samples in this study were 14 old patients who got hypertension. They were divided into 2 groups, one of the groups was treated with communication back massage and the other one was only treated with back massage. The independent variable was communication back massage and back massage. The dependent variable was blood pressure, which was observed for 5 days. Data were collected using aneroid sphygmomanometer and observation paper then analysis was implemented using Paired t-test with level significance α≤0.05 and Independent t-test with level significance α≤0.05. Result: The result showed that blood pressure decrease in significantly both in group one and group two (p=0.04 in group one and p=0.046 in group two). Between the group one and the group two, there was no difference on blood pressure reduction (p=0.315). Discussion: Communication back massage and back massage have a same effect on blood pressure reduction in old patient who get hipetension. The possible explanation for these findings is that communication back massage and back massage have a relaxation effect that can decrease norepinefrin, decrease ADH and increase endorphine. The decrease of norepinephrine can widen blood vessel. The decrease of ADH can reduce excessive fluid in the blood circulation. The increase of endhorphine can reduce sympathetic nerve activity. Therefore, blood pressure level will be decreased.